Hepatoprotective Effect of Oplopanax elatus Nakai Adventitious Roots Extract by Regulating CYP450 and PPAR Signaling Pathway - Jiang, Xiao-Long; Luo, Pan-Yue; Zhou, Yan-Ying; Luo, Zhi-Hui; Hao, Yue-Jun; Fan, Ming-Zhi; Wu, Xiao-Han; Gao, Hao; Bi, Hui-Chang; Zhao, Zhi-Bin; Lian, Mei-Lan; Lian, Zhe-Xiong (Frontiers in Pharmacology, 2022)
Oplopanax elatus Nakai (O. elatus) is a traditional medicine that has been confirmed to exert effective antioxidant and anti-inflammatory functions, and is used for the treatment of different disorders. However, its potential beneficial effects on drug induced hepatotoxicity and relevant molecular mechanisms remain unclear. This study investigated the protective effect and further elucidated the mechanisms of action of O. elatus on liver protection. O. elatus chlorogenic acids-enriched fraction (OEB), which included chlorogenic acid and isochlorogenic acid A, were identified by HPLC-MS/MS. OEB was administrated orally daily for seven consecutive days, followed by a single intraperitoneal injection of an overdose of APAP after the final OEB administration. The effects of OEB on immune cells in mice liver were analyzed using flow cytometry. APAP metabolite content in serum was detected using HPLC-MS/MS in order to investigate whether OEB affects CYP450 activities. The intestinal content samples were processed for 16s microbiota sequencing. Results demonstrated that OEB decreased alanine aminotransferase, aspartate aminotransferase contents, affected the metabolism of APAP, and decreased the concentrates of APAP, APAP-CYS, APAP-NAC by inhibiting CYP2E1 and CYP3A11 activity. Furthermore, OEB pretreatment regulated lipid metabolism by affecting the peroxisome proliferator-activated receptors (PPAR) signaling pathway in mice and also increased the abundance of Akkermansia and Parabacteroides. This study indicated that OEB is a potential drug candidate for treating hepatotoxicity because of its ability to affect drug metabolism and regulate lipid metabolism.